A molecular phylogeny of the parasitoid wasp subfamily Rogadinae (Ichneumonoidea: Braconidae) with descriptions of three new genera. (26th July 2021) - Quicke, Donald L. J.; Fagan‐Jeffries, Erinn P.; Jasso‐Martínez, Jovana M.; Zaldívar‐Riverón, Alejandro; Shaw, Mark R.; Janzen, Daniel H.; Hallwachs, Winnie; Smith, M. Alex; Hebert, Paul D. N.; Hrcek, Jan; Miller, Scott; Sharkey, Michael J.; et al.
Abstract: A molecular phylogeny of the subfamily Rogadinae is presented for 469 species in 52 genera representing all tribes and subtribes. The data comprise cytochrome c oxidase I sequences (DNA barcodes), together with a broad representation of 28S rDNA D2‐D3 expansion region, EF1‐α gene and 16S rDNA fragments. To test monophyly, most genera were represented by multiple species. The analysis of the complete dataset recovered a monophyletic Rogadinae with low support. All six tribes were recovered as monophyletic with the following relationships: (Rogadini, (Stiropiini, (Clinocentrini, (Betylobraconini, [Yeliconini, Aleiodini])))). Three new genera are recognized: Afrorogas Quicke gen.n. (type species Afrorogas copelandi Quicke sp.n. ) for a mainland Afrotropical species; Amanirogas Quicke gen.n. (type species Amanirogas isolatus Quicke sp.n. ), previously treated as a Rogas species from Tanzania; and Papuarogas Quicke gen.n. (type species P . dameni Quicke sp.n. ), for species from Papua New Guinea. Iporhogas Granger is synonymized with Troporhogas Cameron. The African genera Myoporhogas Brues, Scoporogas van Achterberg and the endemic New Zealand genus Rhinoprotoma van Achterberg are synonymized with Aleiodes . A formal diagnosis of the Aleiodini Muesebeck is provided for the first time. This published work has been registered on ZooBank, http://zoobank.org/urn:lsid:urn:lsid:zoobank.org:pub:F24DC64C‐54B7‐45DA‐AB8E‐52DC3E34545C Abstract : Parasitoid wasps mainly attack larvae of other insects with their larvae ultimately killing the single host. They are therefore of great ecological importance through their foodweb interactions. Rogadine parasitoid wasps are of great evolutionary interest because their mode of biology makes them particularly likely to have associated reliable host records. Sequences from four gene regions were used to produce the most comprehensive phylogeny of rogadine including representatives of 95% of the 54 recognized genera. The subfamily and all its tribes were recovered as monophyletic. Relationships between and within tribes are discussed. Two new genera and one subgenus are described as new. Host relationships are summarized. Several genera of Rogadini appear to be specialized on Zygaenoidea but have incorporated some morphologically similar hosts into their host range.